Levels, distribution profiles and risk assessment of chlorinated organophosphate esters in car and road dust from Basrah, Iraq - Layla Salih Al-Omran; Banan Baqer Hashim; William A. Stubbings; Stuart Harrad (Emerging Contaminants)
The occurrence, concentrations, and distribution profiles of chlorinated organophosphate esters (Cl-OPEs) were investigated in seventy-one car and road dust samples collected from Basrah, southern Iraq. In addition, estimated daily intakes (EDIs) via dust ingestion were assessed for toddlers, regular adults, and taxi drivers. In car dust samples, the concentrations of Σ3Cl-OPEs ranged from 4120 to 73200 ng/g (median 11700 ng/g) with tris (1,3-dichloroisopropyl) phosphate (TDCIPP) the predominant compound. In road dust samples, the concentrations of Σ3Cl-OPEs ranged from 269 to 3400 ng/g (median 373 ng/g) and 114–526 ng/g (median 222 ng/g) in urban and rural areas, respectively, with tris (2-chloroisopropyl) phosphate (TCIPP), predominant. Concentrations of Cl-OPEs in urban road dust are significantly higher (P < 0.05) than those in rural road dust, suggesting commercial and industrial activity, population density, and heavy traffic may influence the concentrations. The different compositional profiles of Cl-OPEs in car and road dust may be attributed to the physicochemical properties of Cl-OPEs and the pathways through which they can be released into indoor and outdoor environments. EDI values of Cl-OPEs for the Iraqi population via car dust ingestion were in the order: toddlers > taxi drivers > regular adults, exceeding those via road dust by factors of 27 and 40 from urban and rural dust, respectively. For people who work as taxi drivers, EDIs were seven times higher than those of regular adults, implying that people - such as professional drivers - who spend a substantial amount of time in their vehicles may be exposed to hazardous levels of Cl-OPEs. Despite the study showing that the EDIs through dust ingestion for the three population groups were well below the reference dose (RfD) levels, further studies are recommended to assess other pathways, such as inhalation, dietary sources, and dermal absorption.